Assuring quality sweetpotato planting material. Does inspection make sense? - International Potato Center (2014)
In contrast to seed for grain crops, vegetatively propagated crops such as sweetpotato have bulky and perishable planting material. This presents technical and logistical challenges for an inspection and certification system. We are advocating for an integrated approach for quality assurance mechanisms for sweetpotato planting material based on: support for breeding for virus resistance and virus diagnostics; capacity strengthening of multipliers and farmers for pest and disease identification and management, including rouging (i.e. pulling out visibly affected plants), isolation from other plots, and crop rotation; together with appropriate inspection systems. To ensure sustainability in quality assurance mechanisms, it will be more cost effective for regulatory bodies to concentrate their inspection efforts at the up-stream sources which feed into the seed chain – i.e. pre-basic (foundation) and basic seed.